2018
DOI: 10.1002/pits.22213
|View full text |Cite
|
Sign up to set email alerts
|

Consistently inconsistent: An examination of the variability in the identification of emotional disturbance

Abstract: The federal definition of emotional disturbance (ED) has been heavily criticized as vaguely defined and poorly operationalized yet there has not been a formal analysis of the reliability of the ED criteria. This study examined the reliability of the federal criteria for a special education designation of ED. A total of 179 school psychologists reviewed a mock special education report, made an eligibility determination, and provided information about their eligibility decision. In all, 56 participants found the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It goes without saying that eligibility decisions with this type of mindset are easily influenced by biases. As an illustration, Scardamalia et al (2019) asked 179 school psychologists to use the federal ED definition criteria to make an eligibility determination with a case study and found extremely poor reliability. Policy leaders may need to consider how the ambiguity of the social maladjustment exclusion clause can contribute to patterns of differential access to special education based on where a student lives (intra- and interstate variability).…”
Section: Discussionmentioning
confidence: 99%
“…It goes without saying that eligibility decisions with this type of mindset are easily influenced by biases. As an illustration, Scardamalia et al (2019) asked 179 school psychologists to use the federal ED definition criteria to make an eligibility determination with a case study and found extremely poor reliability. Policy leaders may need to consider how the ambiguity of the social maladjustment exclusion clause can contribute to patterns of differential access to special education based on where a student lives (intra- and interstate variability).…”
Section: Discussionmentioning
confidence: 99%
“…Unchanged since the passage of PL 94-142, experts describe the emotional disturbance definition language as vague and contradictory among a variety of other pejoratives (Sallese et al, 2024). Past research shows extremely poor reliability among school psychologists applying the definition for eligibility decisions (Scardamalia et al, 2019). Vague language within a disability category definition leads to subjective decision making, which is easily influenced by biases (Hanchon & Allen, 2018).…”
mentioning
confidence: 99%
“…The under-identification of students with emotional behavioral disorders may be due to a variety of other reasons beyond perceived stigma or the occurrence of diagnostic substitution. First, diagnostic criteria for emotional disturbance can be overly broad and ambiguous leading to the inconsistent application of criteria in diagnosis (Scardamalia et al, 2019), which may improve with regular, universal screening but widespread screening still does not occur (Bruhn et al, 2014). In addition, internalizing behaviors such as anxiety and depression can go unnoticed (Mitchell et al, 2019), whereas externalizing behaviors tend to manifest in ways that interfere with classroom instruction.…”
mentioning
confidence: 99%